PA-X is a virulence factor in avian H9N2 influenza virus - Gao, Huijie; Liu, Jinhua; Kong, Weili; Sun, Honglei; Pu, Juan; Chang, Kin-Chow; Xu, Guanlong; Sun, Yipeng; Qi, Lu; Wang, Jinliang (Microbiology Society, 2015)
H9N2 influenza viruses have been circulating worldwide in multiple avian species, and regularly infect pigs and humans. Recently, a novel protein, PA-X, produced from the PA gene by ribosomal frameshifting, was demonstrated to be an antivirulence factor in pandemic 2009 H1N1, highly pathogenic avian H5N1 and 1918 H1N1 viruses. However, a similar role of PA-X in the prevalent H9N2 avian influenza viruses has not been established. In this study, we compared the virulence and cytopathogenicity of H9N2 WT virus and H9N2 PA-X-deficient virus. Loss of PA-X in H9N2 virus reduced apoptosis and had a marginal effect on progeny virus output in human pulmonary adenocarcinoma (A549) cells. Without PA-X, PA was less able to suppress co-expressed GFP in human embryonic kidney 293T cells. Furthermore, absence of PA-X in H9N2 virus attenuated viral pathogenicity in mice, which showed no mortality, reduced progeny virus production, mild-to-normal lung histopathology, and dampened proinflammatory cytokine and chemokine response. Therefore, unlike previously reported H1N1 and H5N1 viruses, we show that PA-X protein in H9N2 virus is a pro-virulence factor in facilitating viral pathogenicity and that the pro- or antivirulence role of PA-X in influenza viruses is virus strain-dependent.